Paradygmaty metafilozofii – historia i współczesność - Wawrzynowicz, Andrzej (Człowiek i Społeczeństwo, 2022)
Metaphilosophy as a research discipline is concerned with the overall metatheoretical reflection of philosophy on its own subject matter, assumptions, methodology, and goals guiding this form of human intellectual activity. The aim of this article is to present a cross-sectional analysis of the main stages in the historical development of this discipline, and offer a general characterization of the current state of research. The means to achieving this goal of study is a confrontation between two partly competitive and partly complementary paradigmatic approaches to metaphilosophical reflection which currently determine a relatively wide range of interests in this theoretically promising and heuristically fertile field of philosophical analysis.